Encyclopedia of Life Sciences 2015
DOI: 10.1002/9780470015902.a0003135.pub3
|View full text |Cite
|
Sign up to set email alerts
|

RNA Structure: Tetraloops

Abstract: RNA hairpins are among the most common RNA secondary structural elements and are frequently capped by RNA tetraloops. RNA tetraloops are composed of characteristic four‐loop nucleotides that form a compact and stable structure. While they can be formed by many different nucleotide sequences, UNCG (N = A, C, G, or U), GNRA (R = A or G), and CUUG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Three of the four glycans in 15F3 reside near the end of a stem or in a GNRA tetraloop (specifically GUGA), which is a common natural RNA folding motif . Although this fold has not, to our knowledge, been reported in 2′-fluoro-pyrimidine aptamers, the major hydrogen bonding interactions that confer stability to the tetraloop are all between the purines at the first, third, and fourth positions, with base stacking contributing to stability between the 2–4 bases in the loop in some variations . Therefore, the 2′-fluoro uridine could reasonably be accommodated in the canonical GNRA structure (SI Figure 13).…”
mentioning
confidence: 87%
“…Three of the four glycans in 15F3 reside near the end of a stem or in a GNRA tetraloop (specifically GUGA), which is a common natural RNA folding motif . Although this fold has not, to our knowledge, been reported in 2′-fluoro-pyrimidine aptamers, the major hydrogen bonding interactions that confer stability to the tetraloop are all between the purines at the first, third, and fourth positions, with base stacking contributing to stability between the 2–4 bases in the loop in some variations . Therefore, the 2′-fluoro uridine could reasonably be accommodated in the canonical GNRA structure (SI Figure 13).…”
mentioning
confidence: 87%
“…RNA hairpins play essential structural and functional roles by providing sites for RNA tertiary contacts and protein binding, which facilitates the assembly of ribonucleoprotein particles. More than half of all known RNA hairpins are composed of four nucleotides, called tetra-loops (1)(2)(3)(4)(5). Consequently, RNA tetra-loops are predominant and are commonly found in nature.…”
Section: Introductionmentioning
confidence: 99%
“…The apical loops of domain d in genomes belonging to several viruses of Enterovirus genera were shown by NMR experiments to be tetraloops with a specific spatial structure, which belongs to the UNCG structural class of stable tetraloops ( Du et al, 2003 ; Du et al, 2004 ; Ihle et al, 2005 ; Melchers et al, 2006 ). There are several known structural classes of tetraloops, three of which, named according to consensus sequences, contain tetraloops of extreme stability: UNCG (where N = any nucleotide), GNRA (where R = A/G) and gCUUGc ( Uhlenbeck, 1990 ; Cheong & Cheong, 2010 ). Tetraloops of UNCG and GNRA classes are the most widely represented ( Woese et al, 1990 ; Cheong & Cheong, 2010 ; Bottaro & Lindorff-Larsen, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are several known structural classes of tetraloops, three of which, named according to consensus sequences, contain tetraloops of extreme stability: UNCG (where N = any nucleotide), GNRA (where R = A/G) and gCUUGc ( Uhlenbeck, 1990 ; Cheong & Cheong, 2010 ). Tetraloops of UNCG and GNRA classes are the most widely represented ( Woese et al, 1990 ; Cheong & Cheong, 2010 ; Bottaro & Lindorff-Larsen, 2017 ). Previously, it was shown that only tetraloops of the UNCG structural class, but not tetraloops of GNRA or gCUUGc structural classes, can support effective replication of the poliovirus genome ( Prostova et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%